2020
DOI: 10.2478/aiht-2020-71-3267
|View full text |Cite
|
Sign up to set email alerts
|

Microtubular structure impairment after GSM-modulated RF radiation exposure

Abstract: The objective of the study was to investigate whether low-level 915 MHz GSM-modulated radiofrequency (RF) radiation impairs microtubular structure and affects normal cell growth. V79 cells were exposed to a GSM-modulated field in a Gigahertz Transversal Electromagnetic Mode cell (GTEM cell) for 1, 2, and 3 h. Signal generator combined with power and chip modulator generated the electromagnetic field (EMF). The electric field strength was adjusted to 10, 20, and 30 V/m, and the average specific absorption rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This observation is in conformity with [58]. Most experiments were focused on the effect of EMF on tubular structures [59,60]. However, the results were discussable, mostly depending on EMF.…”
Section: Discussionsupporting
confidence: 81%
“…This observation is in conformity with [58]. Most experiments were focused on the effect of EMF on tubular structures [59,60]. However, the results were discussable, mostly depending on EMF.…”
Section: Discussionsupporting
confidence: 81%
“…Microtubular structure plays a key role in myelination, neuronal cytoskeletal junction, and cell-matrix attachment and has a dramatic effect on brain stiffness ( 26 ). The microtubular structure is also susceptible to EMR, and 915 MHz radiofrequency EMR can disrupt microtubule structures and perturb cell growth ( 27 ). Our transcriptomics data showed that NEMP exposure has the most significant effect on microtubular structures, with biological process terms including axoneme assembly, microtubule bundle formation, microtubule cytoskeleton organization, microtubule-based process, etc.…”
Section: Discussionmentioning
confidence: 99%